(untitled) (Zubía, 2024)
Paleontological prospection campaigns are traditionally planned around previous knowledge of sites that have provided fossils and the interpretation of the regional geology. The application of a suitability index developed for the study of other rock formations (e.g. Two Medicine Formation, in Canada and USA) in the Upper Jurassic deposits of the Lourinhã municipality (Portugal), we determined areas with a higher likelihood of providing tetrapod fossils. The index was built using geospatial data, and through the usage of a weighted sum it was possible to determine the values of the suitability index, and then project them unto a map of the municipality of Lourinhã. The total area of the municipality was divided according to different suitability indexes: lower (overall area of 29,55 km2 ), medium (overall area of 78,56 km2 ) and higher (overall area of 39 km2 ). The application of these methods allows considering distinct factors beyond the geology that can speed up the decision-making process for prospecting and land management.